Persepsi Masyarakat terhadap Kinerja Pemerintah Kabupaten Sambas pada Masa Kepemimpinan Atbah Romin Suhaili Tahun 2016-2020 - Sulaiman Sulaiman; Grace Kelly Sihombing; Anistya Fitri Larasati (Eksos, 2020)
This research was conducted in Sambas Regency. The reason for choosing Sambas Regency was because: (1) the Regent of Sambas was that his period was almost over; (2) The Regent of Sambas as the first regent who hafidz quran. (3) Mr. Atbah Romin Suhaili has a good performance in the government report version. In addition, there are achievements from the Sambas Regency Government, such as zero villages that are very backward, the highest are the achievements of independent villages and others. However, these achievements need to be proven by people's perceptions, because increasing according to the elite level does not necessarily increase according to society. To measure its performance, it uses the mission of the Regent and also the achievements of the Regent as mentioned above, and uses performance indicators, namely productivity, quality, quantity, timeliness, and effectiveness. This type of research used in this research is quantitative research. The research location is located in Teluk Keramat District, which consists of 25 villages. The sampling technique used in this research is proportional sampling, which is based on the number of residents in each village. Data analysis for the questionnaire used an index scale. The overall performance of the Sambas Regency Government during the leadership of Mr. Atbah Romin Suhaili in 2016-2020 was in the good category with an average index of 2.73. These results were obtained based on answers from the community, but there are some notes that need to be improved, namely health insurance that has not been evenly distributed and has not been on target, because of these 2 things that are considered not good by the community. However, related to the achievements expressed by the elite level and also the performance indicators that reached 100% in the 2020 LKJ were also felt by the people of Teluk Keramat.